Analysis of incomplete excisions of basal‐cell carcinomas after breadloaf microscopy compared with 3D‐microscopy: a prospective randomized and blinded study. (17th June 2015) - Boehringer, Alexandra; Adam, Patrick; Schnabl, Saskia; Häfner, Hans‐Martin; Breuninger, Helmut
<x xml:space="preserve">Abstract</x> Basal‐cell carcinomas may show irregular, asymmetric subclinical growth. This study analyzed the efficacy of 'breadloaf' microscopy (serial sectioning) and three‐dimensional (3D) microscopy in detecting positive tumor margins. Two hundred eighty‐three (283) tumors (51.2%) were put into the breadloaf microscopy group; 270 tumors (48.8%) into the 3D microscopy group. The position of any detected tumor outgrowths was identified in clock face fashion. The time required for cutting and embedding the specimens and the examination of the microscopic slides was measured. Patient/tumor characteristics and surgical margins did not differ significantly. Tumor outgrowths at the excision margin were found in 62 of 283 cases (21.9%) in the breadloaf microscopy group and in 115 of 270 cases (42.6%) in the 3D microscopy group, constituting a highly significant difference (p < 0.001). This difference held true with incomplete excision of fibrosing (infiltrative/sclerosing/morpheaform) tumors [32.9% in the breadloaf microscopy group and 57.5% in the 3D microscopy group (p = 0.003)] and also with solid (nodular) tumors [16.1 and 34.2%, respectively (p < 0.001)]. The mean overall examination time required showed no important difference. In summary, for detection of tumor outgrowths, 3D microscopy has almost twice the sensitivity of breadloaf microscopy, particularly in the situation of aggressive/infiltrative carcinomas.